ANALISIS HUKUM TERHADAP PENETAPAN PERGANTIAN JENIS KELAMIN OLEH MAJELIS HAKIM MENURUT HUKUM POSITIF DI INDONESIA (STUDI PENETAPAN NOMOR: 112/PDT.P/2022/PN BLB, PENETAPAN NOMOR 315/Pdt.P/2021/PN.JKT.Utr, DAN PENETAPAN NOMOR 195/Pdt.P/2021/PN.JKT.UTR) - Laila Fairuz Matondang, Nindi; Sembiring, Rosnidar; Aprilyana Sembiring, Idha (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
Determination of gender reassignment by a panel of judges in Indonesia is one of the relevant legal issues in the context of protecting human rights and gender identity diversity. This study aims to analyze the positive legal aspects underlying the determination process, including applicable regulations, practices in the field, and challenges faced in its implementation. A normative legal approach is used to examine related regulations, such as the Criminal Procedure Code, the Law on Religious Courts, and relevant court decisions. The results of the study show that although Indonesia has normatively adopted the concept of protecting gender identity diversity, in practice it faces various obstacles, such as unclear laws, complicated procedures, and a lack of clarity of standards that impact the treatment of transgender individuals. In addition, there is still a mismatch between the principles of human rights protection and the applicable legal process. This study concludes that it is necessary to revise regulations and increase the capacity of judges and other judicial officials so that the process of determining gender reassignment is fairer, more humane, and in accordance with developments in international human rights. Recommendations submitted include the need for harmonization of regulations and strengthening the protection of transgender rights in the Indonesian national legal system.